Profile, Practices, and Challenges of Goat Farming Industry in Talavera, Nueva Ecija: Basis For a Strategic Marketing Plan - Soniga, Joselito; Bernabe, Danica; Bautista, Fhellyze; Guañez, Jennylyn; Taruc, Rollieza Grace; Reyes, Roberto; Abat, Rowena; Perez, Denise; Dela Cruz, Archie (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the market conditions, marketing practices, and operational challenges of goat farming enterprises in Talavera, Nueva Ecija as the basis for developing a strategic marketing plan to improve competitiveness, profitability, and sustainability. Anchored on the concept that effective strategic marketing contributes to enterprise competitiveness and long-term sustainability, the study analyzed goat farming enterprises in terms of business profile, marketing practices, and market-related challenges. A descriptive research design was utilized, involving 54 goat farming enterprise owners selected through purposive random sampling. Data were gathered using a structured survey questionnaire validated for reliability through Cronbach’s Alpha and analyzed using frequency, percentage, and mean statistical tools. Findings revealed that most goat farming enterprises were small-scale, newly established, and financed through personal savings under sole proprietorship management. Farmers commonly raised hybrid and native goats within limited farm areas. Marketing practices emphasized direct selling, maintaining goat quality, fair pricing, and traditional promotional approaches such as word-of-mouth marketing. Seasonal demand, consumer preference for healthy and heavier goats, competition, and livestock-related risks such as theft and natural events were identified as major challenges affecting operations. The study further showed that farmers relied heavily on traditional pricing and marketing systems with limited use of digital promotion and formal market analysis. The study concluded that strategic marketing practices, proper production management, effective pricing, improved promotion, strengthened distribution systems, and risk management are essential in enhancing the competitiveness and sustainability of goat farming enterprises. The proposed strategic marketing plan focused on improving goat care, pricing strategies, digital marketing adoption, market participation, financial management, and operational efficiency to strengthen long-term enterprise growth. The study supports Sustainable Development Goals (SDGs) such as SDG 1 (No Poverty), SDG 2 (Zero Hunger), SDG 8 (Decent Work and Economic Growth), and SDG 9 (Industry, Innovation and Infrastructure) by promoting sustainable livestock enterprises, food security, entrepreneurship, and rural economic development. Its sustainability impact lies in strengthening rural livelihood opportunities, improving agricultural enterprise resilience, supporting local food systems, and providing data-driven insights for sustainable agricultural planning and community development.